Determination of endocrine disruptive phenolic compounds by gas chromatography mass spectrometry after multivariate optimization of switchable liquid-liquid microextraction and assessment of green profile - Karayaka, Sena; Chormey, Dotse Selali; Firat, Merve; Bakirdere, Sezgin (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
This study presents an accurate method for the determination of alkyl phenols and bisphenol A at trace levels using gas chromatography mass spectrometry after preconcentration with switchable liquid-liquid microextraction. In order to achieve high extraction output, the environmentally friendly switchable liquid-liquid microextraction method was optimized by varying parameters such as amount of switch able solvent, sodium hydroxide concentration/amount and the mixing period in a Box-Behnken experimental design. Under optimum extraction conditions, the limits of detection calculated for the analytes were between 0.13 and 0.54 ng/mL. The analytes showed good linearity over broad calibration ranges, and low percent relative standard deviations established good precision. Spiked recovery studies were performed on municipal wastewater and tap water to determine the method's suitability and accuracy, and the results (87-106%) obtained were satisfactory. Bisphenol A was detected (4.0-14 ng/mL) in four plastic samples investigated under high temperature conditions. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Endocrine disrupting compounds; Alkylphenols; Bisphenol A; Switchable liquid-liquid microextraction; Gas chromatography mass spectrometry; BISPHENOL-A; ALKYLPHENOL ETHOXYLATES; HUMAN EXPOSURE; WATER; EXTRACTION; SAMPLES; FATE; DERIVATIVES; Environmental Sciences & Ecology